Simultaneous Bilateral Phacoemulsification and Cataract Extraction : A New Operation Method - Järvenpää, Janne J.; Pape, Bernd; Vesti, Eija (Scholars.Direct, 2023)
Purpose: To investigate the safety of a new simultaneous bilateral phacoemulsification and cataract extraction method. Setting: Two public hospitals and two private hospitals, Finland. Design: Four center retrospective cohort study. Methods: The study group consisted of all simultaneous bilateral phacoemulsification and cataract extraction operations conducted between 2009-2019 by one senior surgeon at one public hospital (2648 eyes) and at two private hospitals (1152 and 932 eyes). The control group was immediately sequential bilateral cataract surgeries (ISBCS) performed at one public hospital by several senior surgeons between 2017-2018 (4854 eyes). The primary outcome was the difference in incidences of early postoperative complications in individuals. Secondary outcomes included intraoperative complications and re-operations due to complications. Results: The study group was non-inferior in all the controlled postoperative complications compared to ISBCS (p < 0.05) at both the 0-3 months and 0-12 months follow-up, except for cystic macular edema (CME) (p = 0.08) that tended to be more common in the study group at 0-12 months. There were no differences in intraoperative complications between the study group and the control group (p = 0.68). Conclusion: The studied simultaneous bilateral phacoemulsification and cataract extraction method is non-inferior to the prevailing standard technique of ISBCS.
Keywords: cataract; surgical treatment; ophthalmology; eye diseases; patient security; eye surgery; fi=Matematiikka|en=Mathematics|